Fiscal Transparency, Fiscal Performance and Credit Ratings - Escolano, Julio (IMF Working Papers; Working Paper ;, 2012)
This paper investigates the effect of fiscal transparency on market assessments of sovereign risk, as measured by credit ratings. It measures this effect through a direct channel (uncertainty reduction) and an indirect channel (better fiscal policies and outcomes), and it differentiates between advanced and developing economies. Fiscal transparency is measured by an index based on the IMF's Reports on the Observance of Standards and Codes (ROSCs). We find that fiscal transparency has a positive and significant effect on ratings, but it works through different channels in advanced and developing economies. In advanced economies the indirect effect of transparency through better fiscal outcomes is more significant whereas for developing economies the direct uncertainty-reducing effect is more relevant. Our results suggest that a one standard deviation improvement in fiscal transparency index is associated with a significant increase in credit ratings: by 0.7 and 1 notches in advanced and developing economies respectively.